Burkholderia phytofirmans PsJN reduces impact of freezing temperatures on photosynthesis in Arabidopsis thaliana - Su, Fan; Jacquard, Cédric; Villaume, Sandra; Michel, Jean; Rabenoelina, Fanja; Clément, Christophe; Barka, Essaid A.; Dhondt-Cordelier, Sandrine; Vaillant-Gaveau, Nathalie (Frontiers in Plant Science, 2015)
Several plant growth-promoting rhizobacteria (PGPR) are known to improve plant tolerance to multiple stresses, including low temperatures. However, mechanisms underlying this protection are still poorly understood. The aim of this study was to evaluate the role of the endophytic PGPR, Burkholderia phytofirmans strain PsJN (Bp PsJN), on Arabidopsis thaliana cold tolerance using photosynthesis parameters as physiological markers. Under standard conditions, our results indicated that Bp PsJN inoculation led to growth promotion of Arabidopsis plants without significant modification on photosynthesis parameters and chloroplast organization. However, bacterial colonization induced a cell wall strengthening in the mesophyll Impact of inoculation modes (either on seeds or by soil irrigation) and their effects overnight at 0, -1 or -3°C, were investigated by following photosystem II (PSII) activity and gas exchanges. Following low temperatures stress, a decrease of photosynthesis parameters was observed. In addition, during three consecutive nights or days at -1°C, PSII activity was monitored. Pigment contents, RuBisCO protein abundance, expression of several genes including RbcS, RbcL, CBF1, CBF2, CBF3, ICE1, COR15a, and COR78 were evaluated at the end of exposure. To assess the impact of the bacteria on cell ultrastructure under low temperatures, microscopic observations were achieved. Results indicated that freezing treatment induced significant changes in PSII activity as early as the first cold day, whereas the same impact on PSII activity was observed only during the third cold night. The significant effects conferred by PsJN were differential accumulation of pigments, and reduced expression of RbcL and COR78. Microscopical observations showed an alteration/disorganization in A. thaliana leaf mesophyll cells independently of the freezing treatments. The presence of bacteria during the three successive nights or days did not significantly improved A. thaliana responses but prevented the plasmalemma disruption under freezing stress.